ANÁLISE BIOQUÍMICA DOS CONSTITUINTES ORGÂNICOS E INORGÂNICOS DO PLASMA SEMINAL DE CUTIAS - Pereira, Ana Glória; Dantas, Maiko Roberto Tavares; Moreira, Samara Sandy Jerônimo; Luz, Náyra Rachel Nascimento; Silva, Alexandre Rodrigues (Ciência Animal, 2021)
The objective of the present study was to identify the biochemical components of the agoutis’ seminal plasma. For this purpose, six adult males were collected by means of electroejaculation. Biochemical analysis was performed using commercial kits and the absorbances were read on a spectrophotometer. The results were described as mean and standard error. The following organic constituents were identified in the seminal plasma: albumin (6.64 ±2.31g/dL), total proteins (1.9±0.62g/dL), glucose (26.27±9.84mg/dL), fructose (26.92±8.08mg/dL), citric acid (408.28±227.92mg/dL)), triglycerides (282.04±83.58mg/dL) and cholesterol (125.16±34.35mg/dL). Regarding inorganic components, chlorides (283.66±104,11mEq/L), magnesium (4.24±0.38mg/dL), phosphorus (3.67±0.59mg/dL), calcium (12.47±1.85mg/dL), and iron (620.63±266.33µg/dL). It should be noted that this is the first description of the biochemical composition of seminal plasma in the species Dasyprocta leporina. This information will be useful for the improvement of sperm conservation protocols for the species.